No evidence for the involvement of the argasid tick Ornithodoros faini in the enzootic maintenance of marburgvirus within Egyptian rousette bats Rousettus aegyptiacus. Issue 1 (December 2016) - Schuh, Amy; Amman, Brian; Apanaskevich, Dmitry; Sealy, Tara; Nichol, Stuart; Towner, Jonathan
Abstract Background The cave-dwelling Egyptian rousette bat (ERB;Rousettus aegyptiacus ) was recently identified as a natural reservoir host of marburgviruses. However, the mechanisms of transmission for the enzootic maintenance of marburgviruses within ERBs are unclear. Previous ecological investigations of large ERB colonies inhabiting Python Cave and Kitaka Mine, Uganda revealed that argasid ticks (Ornithodoros faini ) are hematophagous ectoparasites of ERBs. Yet, their potential role as transmission vectors for marburgvirus has not been sufficiently assessed. Findings In the present study, 3, 125O. faini were collected during April 2013 from the rock crevices of Python Cave, Uganda. None of the ticks tested positive for marburgvirus-specific RNA by Q-RT-PCR. The probability of failure to detect marburgvirus at a conservative prevalence of 0.1 % was 0.05. Conclusions The absence of marburgvirus RNA inO. faini suggests they do not play a significant role in the transmission and enzootic maintenance of marburgvirus within their natural reservoir host.